2011
DOI: 10.3109/17435390.2011.629747
|View full text |Cite
|
Sign up to set email alerts
|

TiO2nanoparticles induce oxidative DNA damage and apoptosis in human liver cells

Abstract: Titanium dioxide nanoparticles (TiO(2) NPs), widely used in consumer products, paints, pharmaceutical preparations and so on, have been shown to induce cytotoxicity, genotoxicity and carcinogenic responses in vitro and in vivo. The present study revealed that TiO(2) NPs induce significant (p < 0.05) oxidative DNA damage by the Fpg-Comet assay even at 1 µg/ml concentration. A corresponding increase in the micronucleus frequency was also observed. This could be attributed to the reduced glutathione levels with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(155 citation statements)
references
References 41 publications
9
145
1
Order By: Relevance
“…In addition, a future study is necessary to explore the long-term effect of fatty acids on TiO 2 NP-induced toxicity to represent more realistic subchronic or chronic exposure. Moreover, it is important to verify the protective role of fatty acid composites against adverse effects of TiO 2 NPs by other types of toxicity measures, such as the comet assay (Bhabra et al, 2009;Shukla et al, 2013). Also, it remains to be examined whether or not these beneficial effects of surface modification also exist in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a future study is necessary to explore the long-term effect of fatty acids on TiO 2 NP-induced toxicity to represent more realistic subchronic or chronic exposure. Moreover, it is important to verify the protective role of fatty acid composites against adverse effects of TiO 2 NPs by other types of toxicity measures, such as the comet assay (Bhabra et al, 2009;Shukla et al, 2013). Also, it remains to be examined whether or not these beneficial effects of surface modification also exist in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 To investigate whether the incubation of HEK293 cells with Y 2 O 3 NPs was associated with cell apoptosis, we performed flow cytometry. Consistent with our MTT and LDH assays, we found that incubation with Y 2 O 3 NPs was associated with the induction of cell apoptosis (at 24 hours) and necrosis (at 48 hours; Figure 4A-4D).…”
Section: Discussionmentioning
confidence: 99%
“…3,46,47]. Endogenous ROS are indispensable for everyday life, as highlighted by their involvement in signal transduction and the initiation of the innate immune system (effectors produced to destroy pathogens and to control cellular responses).…”
Section: Discussionmentioning
confidence: 99%